Situación laboral de los profesionales de enfermería de instituciones de salud, municipio de Medellín, 1999 (2001)
ABSTRACT: Descriptive exploratory study of active working nursing professionals. It attempts to identify transformations produced in the form of health services, which find their origin in labor and health system reforms; its aim is the preparation of proposals favoring both working conditions and the scientific and technical level. Questions were made on sociodemographic aspects, professional activity, participation in social security and satisfaction at work (Likert´s scale) Findings: 96,7% are women. Main area of work: assistance-administrative, 64%; ambulatory and community, 3,2%, and private practice, 4%. Participation in publications and research, 18,2%. A graduate level of education has been reached by 20,7% of the professionals; 68% take two or fewer continuing education courses every year. Hierarchical dependence is still a nursing department, in 70% of the cases; 73,3% of the resources are located in institutions of a third level of complexity. The modalities of contract and affiliation to the Social Security are better in private institutions; la lack of satisfaction at work is higher in public institutions. Health sector human resource policies have slowed down the progress of nursing in aspects of professional development. The current health service model has deteriorated working conditions.